PRODUCTION OF CLEAN DIESEL OILS - A.S. Nasution; E. Jasjfi; Evita H. Legowo (Testing Center for Oil and Gas LEMIGAS, 2005)
Cars and fuels have been developed simultaneously and nowadays cars demand a very sophisticated fuel indeed. Environmental restriction and efforts to minimize the pollution problem by exhaust gases are causing de- sign changes in cars that in turn are having some effects on fuel quality. The development of processes for making high cetane number gas oil blending components and the widespread use of additives to enhance fuel properties have all contributed to the highly developed motor fuel used today